2011
DOI: 10.1007/s00107-011-0561-z
|View full text |Cite
|
Sign up to set email alerts
|

One press cycle production of fiberboard with unsymmetrically distributed densities

Abstract: With an arrangement of two different densities in a fiberboard according to the newly developed Dascanova Technology a significant amount of raw material could be saved. In this part of the study a production possibility of fiberboard with dual density was investigated. The aim of this research is to produce the highest possible difference between densities formed in one press process. Various methods described by different resin systems, additives, moisture contents and modified raw materials were used for th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 5 publications
0
2
0
Order By: Relevance
“…A board with a double density difference between two horizontal layers of fiber mat was obtained in one press cycle at two different moisture content (Haas and Frühwald 2000). By applying a new technology with the commercial description Dascanova Technology, a selective arrangement of the fiberboard density did achieve in one press cycle (Déneši et al 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A board with a double density difference between two horizontal layers of fiber mat was obtained in one press cycle at two different moisture content (Haas and Frühwald 2000). By applying a new technology with the commercial description Dascanova Technology, a selective arrangement of the fiberboard density did achieve in one press cycle (Déneši et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, research on production and characterization of the tubular/ extruded fiberboard is scarce, although, a patent for the production process of extruded fiberboard date back to 1956 (Bowers et al 1956). It was recently showed that MDF produced with special forming has significantly higher bending properties compared to those panel with conventional forming (Ohba et al 2001, Déneši et al 2012. Hence, developing a cost-efficient lightweight MDF with high rigidity for application in furniture manufacture, building, transport and exhibition construction as well as for direct painting and printing is necessary today.…”
Section: Introductionmentioning
confidence: 99%